Prospects of generation Z in the labor market of Kazakhstan - Talapbayeva, G.E.; Yerniyazova, Zh.N.; Kultanova, N.B.; Zhumatayeva, A.R. (BUKETOV BUSINESS REVIEW, 2023)
Object: As part of the research of the scientific work, the main goal was to revise the employment policy in connection with structural global changes and the volatility of the world economy as a whole, and in particular with demographic changes that affected the national labor market of Kazakhstan, as well as to determine the role and place of generation Z in the formation of the future labor market. Methods: In the course of writing a scientific article, the following research methods were used: statisticaleconomic, dialectical and comparative methods. Findings: By 2030, 37% of the workforce in Kazakhstan will represent generation Z. Considering that the Republic of Kazakhstan, according to official statistics, is a fairly “young” country, where the average age of the population is 31.94 years. 33.97% of our compatriots are children under the age of 17, 19.72% are young people aged 14-28, then in the medium term, generation Z will have a share of the income of the entire economy of the country of more than 25% in 2030. Conclusions: The environmental and digital transition should be based on a broader approach to digital culture, combined with promoting the acquisition of appropriate technical skills by young people so that they can fully use them to benefit from the new opportunities created. At the same time, efforts to build a more sustainable future require the creation of working conditions by the state, but also the active participation and significant contribution of young people.